1999
DOI: 10.1002/(sici)1096-8644(199909)110:1<17::aid-ajpa2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Fatal attraction: Interest in infants and infant abuse in rhesus macaques

Abstract: This study investigated whether infant abuse by female rhesus macaques (Macaca mulatta) is a phenomenon specific to their own offspring or reflects a general tendency to interact negatively with infants. Several aspects of the relationship between maternal behavior, infant handling, and infant harassment were also investigated. Study subjects were 20 group-living rhesus mothers with their infants observed during the first 12 weeks of lactation. The results of this study indicate that abusive mothers are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Rather, abusive behavior appears to be a stable maternal characteristic that is likely to be displayed with young infants, irrespective of whether they are the mother's own offspring or foster infants. Interestingly, a recent study demonstrated that infant abuse in rhesus macaques does not reflect a tendency to interact negatively with infants in general (Maestripieri, 1999b). For example, abusive mothers did not interact negatively with other females' infants more than did control mothers.…”
Section: Discussionmentioning
confidence: 97%
“…Rather, abusive behavior appears to be a stable maternal characteristic that is likely to be displayed with young infants, irrespective of whether they are the mother's own offspring or foster infants. Interestingly, a recent study demonstrated that infant abuse in rhesus macaques does not reflect a tendency to interact negatively with infants in general (Maestripieri, 1999b). For example, abusive mothers did not interact negatively with other females' infants more than did control mothers.…”
Section: Discussionmentioning
confidence: 97%
“…Though several studies have explored the adaptive significance of allomaternal behavior by young female primates toward infants (Quiatt, 1979, Meaney et al, 1990), the exact relationship between interest in infants and maternal behavior remains unresolved (Maestripieri, 1999). Historically, young females’ interest in infants is thought to provide the substrate through which they gain experience necessary for mothering their own offspring (Lancaster, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, allomothering can be costly to mothers, as some females can abuse infants or refuse to return them to mothers. This is particularly likely to occur in species where females form steep and despotic dominance hierarchies (Schino et al, 1993;Maestripieri, 1999;Ross & MacLarnon, 2000). Indeed, Ross & MacLarnon (2000) hypothesized that female-female competition limits the occurrence of allomaternal care across species.…”
Section: Pathway 1: Communal Care Of Offspring and Allomotheringmentioning
confidence: 99%